Effect of the covered-rearing with plastic film on the growth and development of grown silkworm - SHI Lian-gen; ZHOU Jin-qian (浙江大学学报. 农业与生命科学版)
Effects of the plastic film covered rearing with two feedings a day on the growth and development of grown silkworm (4-5 instar) were studied in this paper. Results showed that under conditions of covering with plastic film for 10-20 h per day and decreasing feeding times from 4 times per day to 2 times per day in grown silkworm stage, no any negative effects on the duration of 4th instar, body weight, molting regularity, ingestion and digestion of mulberry leaves, leaf-silk conversion rate, yield and quality of cocoon were found except that duration of 5th instar were cutted shord 2 h, and that the someitems shell slightly increased. It was feasible to covering with plastic filmfor 10-20 h per day and decreasing feeding times to two times per day if a proper rearing management was accepted.